Simultaneous Quantitation of Lipid Biomarkers for Inflammatory Bowel Disease Using LC–MS/MS - Yashpal S. Chhonker; Shrey Kanvinde; Rizwan Ahmad; Amar B. Singh; David Oupický; Daryl J. Murry (Metabolites, 2021)
Eicosanoids are key mediators and regulators of inflammation and oxidative stress that are often used as biomarkers for severity and therapeutic responses in various diseases. We here report a highly sensitive LC-MS/MS method for the simultaneous quantification of at least 66 key eicosanoids in a widely used murine model of colitis. Chromatographic separation was achieved with Shim-Pack XR-ODSIII, 150 × 2.00 mm, 2.2 µm. The mobile phase was operated in gradient conditions and consisted of acetonitrile and 0.1% acetic acid in water with a total flow of 0.37 mL/min. This method is sensitive, with a limit of quantification ranging from 0.01 to 1 ng/mL for the various analytes, has a large dynamic range (200 ng/mL), and a total run time of 25 min. The inter- and intraday accuracy (85–115%), precision (≥85%), and recovery (40–90%) met the acceptance criteria per the US Food and Drug Administration guidelines. This method was successfully applied to evaluate eicosanoid metabolites in mice subjected to colitis versus untreated, healthy control mice. In summary, we developed a highly sensitive and fast LC−MS/MS method that can be used to identify biomarkers for inflammation and potentially help in prognosis of the disease in inflammatory bowel disease (IBD) patients, including the response to therapy.